Historical research through generative artificial intelligence presence and role of American women in the Spanish Civil War - Navarro Férez, Javier; Orduña Prada, Mónica (Ebre 38, 2026)
This article examines the role of American women in the Spanish Civil War, aiming to explore their significance within the conflict. The methodology combines generative artificial intelligence tools with the analysis of primary sources, academic literature, scientific articles, and digital archives. The findings highlight the essential contribution of these women as nurses, correspondents, and activists, emphasizing their humanitarian and journalistic involvement on the Republican front. The research underscores their position as key figures in the international mobilization against fascism.
Investigación histórica a través de la inteligencia artificial generativa: presencia y papel de las mujeres estadounidenses en la Guerra Civil Española.
Este artículo examina el papel de las mujeres estadounidenses en la Guerra Civil Española, con el objetivo de explorar su importancia dentro del conflicto. La metodología combina herramientas de inteligencia artificial generativa con el análisis de fuentes primarias, literatura académica, artículos científicos y archivos digitales. Los hallazgos resaltan la contribución esencial de estas mujeres como enfermeras, corresponsales y activistas, enfatizando su participación humanitaria y periodística en el frente republicano. La investigación subraya su posición como figuras clave en la movilización internacional contra el fascismo.
Keywords: generative artificial intelligence; women; Spanish civil war; international brigades; international solidarity; inteligencia artificial generativa; mujeres; guerra civil española; brigadas internacionales; solidaridad internacional